Technological factors and adoption of green innovation: Moderating role of government intervention: a case of SMEs in Pakistan - Shazia Kousar; Pirzada Sami Ullah Sabri; Mahwish Zafar; Adeel Akhtar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The purpose of this study is twofold; one is to measure the size of the impact of technological factors on the adoption of green innovations in SMEs and second is to test the moderating role of government intervention between technological factors and adoption of green innovations. Technological factors consist of complexity, compatibility, relative advantage and tri-ability of green innovations while green innovations are new environment friendly methods of production. The self-administrative survey approach was used to collect the data through the questionnaire. The random probability sampling technique was used to collect the data from managers, senior executives, and technicians of SMEs. Multiple regression analysis was employed to measure the relationship and size of the impact of technological factors on the adoption of green technology. In addition, a hierarchical regression is used to investigate the moderating role of government intervention between technological factors and adoption of green technology. The results suggest that the complexity of technology negatively and significantly affects the adoption of green technology while relative advantages and tri-ability positively and significantly affect adoption of green technology. The results of hierarchical regression analysis indicate that government intervention significantly moderates between complexity, relative advantages, tri-ability, and adoption of green technology. Considering the importance of green innovations in the reduction of global warming, policy makers can get benefit from the evidence of this study and can take necessary measures to increase the possibilities of adoption of green innovations in SMEs.
Keywords: 330; green innovation; green technology; complexity; compatibility; relative advantage; tri-ability; government intervention